Cooperation and Communication Management of Vocational High School Internship Program with World Business Industry - Waradzi Mustakim; Nizwardi Jalinus; Jonni Mardizal (Universitas Pahlawan Tuanku Tambusai, 2023)
The goal of this study was to ascertain how apprenticeship programs in vocational high schools would be managed in terms of cooperation and communication. Research is conducted using descriptive qualitative methods. Techniques for gathering data include observation, interviews, and documentation studies. Techniques for data analysis include data reduction, data display, inference, and recommendation gathering. The findings revealed: (1) management of school partnerships with business and industry in the Computer and Network Engineering Department at SMK Negeri 1 Tilatang Kamang; (2) forms of partnership such as curriculum adaptation to business and industry, apprenticeships, vocational competency testers, employment by business and industry, and industrial visits; (3) Factors encouraging the partnership include a shared vision and mission, mutually beneficial interests between schools and business and industry, the school committee's ability and support, and the availability of facilities and infrastructure. (4) Factors inhibiting partnerships include divergent perspectives between schools and business and industry, the presence of ineffective teachers, a lack of time and money, and other factors. (5) Strategies for overcoming challenges include opening lines of communication, looking for funding, enlarging the network of partners, and offering internships to students.